2001
DOI: 10.1517/14656566.2.7.1137
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept in rheumatoid arthritis

Abstract: Etanercept (Enbrel, Immunex Corporation, Seattle, Washington, USA) is a new biological disease-modifying antirheumatic drug (DMARD) for the treatment of active rheumatoid arthritis (RA). It is one of two TNF-alpha blockers to be licensed for the treatment of active RA and is classified as a recombinant human soluble TNF receptor. The drug competitively inhibits the binding of TNF to cell surface receptors and thus renders TNF biologically inactive. In doing so, etanercept inhibits the pro-inflammatory effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…2,28,29) Thus far, only two drugs targeting TNF-a were developed and licensed to clinically treat rheumatoid arthritis patients, in a form of modified protein of soluble TNF receptor or monoclonal antibody to TNF-a. 30,31) Our results also indicated that those cytokines were significantly secreted in arthritic joints of the legs, which means that the inflammatory cells, mainly macrophages, were infiltrated into the arthritic joints as the arthritis proceeded. Because the inflammatory cytokines such as TNF-a and IL-1b were specifically stained on the bone section, the immunopositive cells could indirectly represent the inflammatory cells infiltrated.…”
Section: Discussionsupporting
confidence: 54%
“…2,28,29) Thus far, only two drugs targeting TNF-a were developed and licensed to clinically treat rheumatoid arthritis patients, in a form of modified protein of soluble TNF receptor or monoclonal antibody to TNF-a. 30,31) Our results also indicated that those cytokines were significantly secreted in arthritic joints of the legs, which means that the inflammatory cells, mainly macrophages, were infiltrated into the arthritic joints as the arthritis proceeded. Because the inflammatory cytokines such as TNF-a and IL-1b were specifically stained on the bone section, the immunopositive cells could indirectly represent the inflammatory cells infiltrated.…”
Section: Discussionsupporting
confidence: 54%
“…The toxic effects of TNF-␣ are mediated via TNFR2 receptors on CD11b ϩ microglia, which are likely to be the final killers of oligodendrocytes and, indirectly, of RGCs. Interference with TNF-␣ by using a blocking antibody has been applied in the treatment of other inflammatory diseases (De Keyser et al, 2006); other possible approaches include the use of a soluble receptor (Alldred, 2001) or a TACE (TNF-␣-converting enzyme) inhibitor (Moss et al, 2001). Blockade of TNF-␣ function and downstream microglial activation may be an important approach for the treatment of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…by OPG or RANK:Fc) is unlikely to be completely successful in the treatment of wear particle-associated bone resorption where inflamed tissues have elevated levels of T N F r and IL-la. Anti-T N F drugs (such as etanercept and infliximab) are currently being used in the treatment of rheumatoid arthritis and have been shown to reduce the formation of marginal erosions [2,57]. They have also been found to inhibit wear-induced osteolysis in experimental animals [9].…”
Section: Discussionmentioning
confidence: 99%